Predictors of poor glycemic control among type 2 diabetes mellitus patients treated with antidiabetic medications: A cross-sectional study in China. Issue 43 (29th October 2021) - Wang, Jingqing; Li, Jie; Wen, Chendong; Liu, Yan; Ma, Hongshan
Abstract : Abstract: This study aimed to clarify of the predictors of poor glycemic control in type 2 diabetes mellitus (T2DM) patients treated with antidiabetic medications in China. This study was a retrospective, cross-sectional study based on SuValue database. T2DM patients aged 18 years or older performing glycosylated hemoglobin A1c (HbA1c) examinations from January 1st, 2018 to December 31st, 2018 were included and have been treated with antidiabetic medications for at least 6 months. HbA1c < 7.0% was defined as adequate glycemic control. Multivariate analysis was performed for the factors associated with poor glycemic control. A total of 13972 T2DM patients were included in this study. The adequate glycemic control rate was 44.04% (n = 6153). In the multivariate analysis, predictors of poor glycemic control include longer T2DM duration (5–10 years vs <5 years and >10 years vs <5 years, odds ratio [OR] = 1.499 and 1.581, P  < .001 and P  = .008), myocardial infarction (OR = 1.141, P  = .041), diabetic neuropathy (OR = 1.409, P  < .001), secondary hospital (OR = 1.877, P  < .001), underdeveloped regions (OR = 1.786, P  < .001), insulin only (OR = 3.912, P  < .001), combination of oral antidiabetic agents and/or insulin use ( P  < .001). In conclusion, longer T2DM duration, secondary hospital, myocardial infarction, diabetic neuropathy, undeveloped regions and use of polypharmacy and insulin were associated with poor glycemic control among T2DM patients treated with antidiabetic medications. Patient education and training of health care providers may be short-term strategy to achieve adequate glycemic control.